Study of Sintering Parameters and Sintering Additives Effect on selected properties of Silicon Nitride - Gabrisova, Zuzana; Brusilova, Alena; Svec, Pavol (Manufacturing Technology Journal, 2019)
The subject of this article is the study of influence of sintering time and sintering additives on mechanical properties and wear resistance. Si3N4 with Al2O3+Y2O3 additives (YAG) and Si3N4 with MgO additives was used as an experimental materials. Compositions sintered for 30 min achieved optimal combination the hardness and fracture toughness - 15.05 GPa and 6.87 MPa.m1/2 for Si3N4-MgO and 14.65 GPa and 5.71 MPa.m1/2 for Si3N4 -YAG. Wear was mostly influenced by the hardness of ceramic materials. The specimen with the highest hardness achieved the highest wear resistance. Wear resistance of ceramics decreased with the grain growth and with the transformation progress of narrow α- Si3N4 phase to prismatic β- Si3N4 phase. The wear resistance of the studied ceramics can be described by model V ~ HV-1. Si3N4 -YAG in comparison to Si3N4-MgO has several times greater wear resistance.
Keywords: silicon nitride; sintering additives; mechanical properties; wear resistance